2015
DOI: 10.1037/pst0000019
|View full text |Cite
|
Sign up to set email alerts
|

A delay-discounting measure of preference for racial/ethnic matching in psychotherapy.

Abstract: In this study, we sought to compare racial/ethnic minority participants' preference for racial/ethnic matching in psychotherapy with preferences for other methods of addressing cultural factors in treatment. Using a delay-discounting method, college students (331 racial/ethnic minority students from 2 universities) and a nationwide sample of self-reported clients (n = 77) were asked to indicate their strength of preference for 4 different methods for addressing culturally related variables in psychotherapy, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 11 publications
2
29
0
1
Order By: Relevance
“…Another method described is to present participants with multiple cases and rank-order their ratings on relevant therapy aspects. Methodologically close to this approach is a delay-discounting measure proposed by Swift et al (2015) allowing for comparisons between two particular characteristics. The more (hypothetical) effectiveness patients sacrifice for any characteristic, the higher their preference.…”
Section: Introductionmentioning
confidence: 99%
“…Another method described is to present participants with multiple cases and rank-order their ratings on relevant therapy aspects. Methodologically close to this approach is a delay-discounting measure proposed by Swift et al (2015) allowing for comparisons between two particular characteristics. The more (hypothetical) effectiveness patients sacrifice for any characteristic, the higher their preference.…”
Section: Introductionmentioning
confidence: 99%
“…Although most clients picked the 70% option at first, on average they switched to the less effective treatment once it reached 30%—thus indicating they were willing to sacrifice 40% in treatment efficacy to ensure that positive relationship. The same method with racial–ethnic participants found that they had much stronger preferences for therapist multicultural training and use of culturally adapted treatments than they did for simple racial–ethnic matching with their therapists (Swift, Callahan, Tompkins, Connor, & Dunn, ). More recently, Boswell and colleagues () used this method to examine preferences for clinician performance information.…”
Section: Definitions and Measuresmentioning
confidence: 99%
“…The second area in counseling preferences, the client preferences (Swift, et al, 2018), which was also called as therapist preferences in the earlier sources as a subfield of client preferences, refers to the preferences regarding the demographic characteristics of the therapist offering psychological assistance (Swift, et al, 2011). However, research suggests that not only demographics, but also assessments about personality traits of the therapist also play a role in this preference (Swift, et al, 2015). The third area of preference in counseling is the therapy preferences.…”
Section: Extended Abstract Introductionmentioning
confidence: 99%